Development and validation of a stability-indicating LC-UV and LC-MS/MS methods for quantitative analysis of anisomycin and identification of degradation products - Ljiljana Tolić; Svetlana Grujić; Mila Laušević (Universidade de São Paulo, 2018)
ABSTRACT Multifunctional drug anisomycin was subjected to forced degradation in accordance with International Conference on Harmonisation (ICH) guidelines for the first time. The drug was exposed to the recommended stress conditions of hydrolysis (acidic, alkaline and neutral), oxidation, thermal stress and photolysis, in order to investigate its stability. Optimized LC-MS/MS method was validated as recommended by ICH Q2(R1) guideline with respect to the specificity, accuracy, precision, limits of detection and quantitation, linearity and robustness. Anisomycin exhibited high instability under alkaline and thermal (neutral hydrolysis) conditions. It showed moderate stability under acidic, neutral, oxidative, thermal (acidic hydrolysis) and photolytic conditions, with the lowest degradation level observed in the case of light and oxidation stress. Formation of the same degradation product, identified as deacetylanisomycin, was observed under all applied stress conditions.